2014
DOI: 10.1073/pnas.1408628111
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and flux reveal a new global view and physical quantification of mammalian cell cycle

Abstract: Cell cycles, essential for biological function, have been investigated extensively. However, enabling a global understanding and defining a physical quantification of the stability and function of the cell cycle remains challenging. Based upon a mammalian cell cycle gene network, we uncovered the underlying Mexican hat landscape of the cell cycle. We found the emergence of three local basins of attraction and two major potential barriers along the cell cycle trajectory. The three local basins of attraction cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
202
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(216 citation statements)
references
References 35 publications
3
202
0
Order By: Relevance
“…30,50 We have shown that the mRNA number is distinctly larger in the case of random division than in the case of constant division, implying that the efficiency is higher in the former case than in the latter case. 30,50 We have shown that the MFPT is shorter in the case of random division than in the case of constant division, and that the MFPT in the case of slow switching is nearly as large as that in the case of fast switching (Fig. 4 Another constraint is in the ability that a gene responds quickly to external stimuli.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…30,50 We have shown that the mRNA number is distinctly larger in the case of random division than in the case of constant division, implying that the efficiency is higher in the former case than in the latter case. 30,50 We have shown that the MFPT is shorter in the case of random division than in the case of constant division, and that the MFPT in the case of slow switching is nearly as large as that in the case of fast switching (Fig. 4 Another constraint is in the ability that a gene responds quickly to external stimuli.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
“…5,6 While quantitative time-lapse fluorescence microscopy allows for tracing the real-time expression of genes in individual cells, [7][8][9] there is considerable interest in theoretically understanding how different molecular mechanisms of gene expression affect variations in mRNA and protein abundances across a population of genetically identical cells. When cellular energy and growth factors are enough, cell growth and division are all periodic events [27][28][29][30] (traditionally, cell division means that a cell begins to divide when its volume reaches twice the original volume, so this kind of division is actually a volume-based division. [17][18][19][20][21][22][23][24][25][26] Cell growth and division are ubiquitous in natural systems.…”
Section: Introductionmentioning
confidence: 99%
“…., X n represent the concentration or number of molecules of species), we expect to have n-coupled differential equations, which are hard to solve analytically. Applying a self-consistent mean field approach (14,(32)(33)(34)(35), we split the probability into the products of individual ones: P X 1 ; X 2 ; . .…”
Section: Self-consistent Mean Field Approximationmentioning
confidence: 99%
“…Therefore, it is not only continuous nonlinear dynamics that is relevant, but it is also stochasticity induced by the paucity of some key molecular regulator(s) in the system. Thus, the notion of stochastic potential is of paramount importance (see Wang et al [13][14][15][16][17][18][19][20][21][22][23]). The role of energy in the establishment and maintenance of living systems at steady-states far from equilibrium is related, but is not addressed here (see Qian et al [24][25][26][27][28][29]).…”
Section: Biochemical Noise Contributes In Subtle Waysmentioning
confidence: 99%